FAKTOR-FAKTOR YANG MEMPENGARUHI PENETAPAN MARGIN MURABAHAH PEMBIAYAAN KONSUMTIF DI BANK KALTIM SYARIAH - Satya, Kenda (Faculty of Economics and Business, University of Muhammadiyah Malang, 2013)
This research was proposed to discover the influential factors on consumptive financing murabahah (a contract of sale of goods with the agreement on selling price and profit earned between the seller and the buyer) margin in Kaltim Sharia bank. The research instrument that had been used was the multiple linear regressions, correlation coefficient, coefficient of determination, as well as the classical assumption. Based on the analysis, the results showed that 1) Variable of Financing Deposit Ratio (X1), Return on Assets (X2), Inflation (X3) and the interest rate (X4) gave significant effect on murabahah margin Bankaltim Sharia (Y) simultaneously. The initial analysis confirmed that the first hypothesis was accepted and proven accurate because the value of probability was less than (<)0.05 namely 0.000; 2) Moreover, the next investigation found that inflation (X3) was the most dominant variable in this study for its Inflation beta value was more than (>)FDR beta value (X1), ROA (X2), and interest rates (X4) which means that the second hypothesis was rejected due to higher inflation would extensively increase production costs and prices of goods / services. Consequently, the purchasing power will decline and subsequently murabahah financing demand would automatically decreasing as well that ultimately results in reduced margins of murabahah.